VIUSID Agro (R) dose effect on the morpho-physiological and productive behavior of radish (Raphanus sativus L.) - Pena Calzada, Kolima; Carlos Rodriguez, Juan; Olivera Viciedo, Dilier [UNESP]; Calero Hurtado, Alexander [UNESP]; Felix Melendrez, Jorge; Garcia Valdez, Rodrigo (Univ Zulia, Facultad Agronomia, 2018)
A randomized block experiment design with five treatments and three replications was used to evaluate the effect of VIUSID Agro (R) on radish (Raphanus sativus L.) cultivation. The variants analyzed were dose 0.2, 0.5, 0.7 and 1.0 L.ha(-1) of the growth promoter and a control. Among the indicators evaluated were the fresh and dry biomasses of the plant as well as its individual organs. In addition, the number of leaves per plant, the polar and equatorial diameter of the fleshy stem, the physiological growth rates as well as the foliar, productive efficiency and the agricultural yield were evaluated. The results showed a significant increase (P <= 0.05) of the fresh biomass of the plant when the VIUSID Agro (R) was used and the increments with respect to the control were on average of 20.65 g. In the dry biomass final evaluation, all treatments with VIUSID Agro (R) differed significantly (P <= 0.05) from the control and exceeded it as an average of 1.14 g. In the fresh and dry biomass of the stems, the 0.7 L.ha(-1) dose was the best behavior. The active growth rate was significantly higher (P <= 0.05) with the mentioned dose. The highest productive efficiency was achieved with the variants 0.7 and 1.0 L.ha(-1) and the best behavior in the yield with significant differences (P <= 0.05) of the rest of the treatments was the dose 0.7 L.ha(-1 )with 1.30 kg.m(-2). In conclusion, VIUSID Agro (R) positively influenced the morpho-physiological and productive indicators of radish cultivation.
Keywords: amino acid; vegetables; organopony; growth promoter; VIUSID Agro (R)